Methodological path to reach the degree of saturation in qualitative research: grounded theory - Cleson Oliveira de Moura; Ítalo Rodolfo Silva; Thiago Privado da Silva; Karoliny Alves Santos; Maria da Conceição Albernaz Crespo; Marcelle Miranda da Silva (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objectives: to achieve the degree of saturation in study that applied the grounded theory. Methods: qualitative research, carried out in four Family Health Units, between June 2018 and May 2019. The data from the interviews with 30 health professionals and non-participant observation were coded in the stages: open, axial and integration. Results: the degree of saturation was achieved by two conceptual models - theoretical saturation and inductive thematic. Theoretical saturation was considered: the development of conceptual codes and observation, in the collection and analysis of data, when they generated new categories/subcategories or only indicated increasing instances. For thematic inductive saturation, the use of new codes based on each interview stood out. Final Considerations: the visual layout for the number of codes, the theoretical scope of the concepts and the delimitation of the sample groups guided the identification of the degree of saturation for the development of the conceptual body that supported the substantive theory.